Self‐reported marijuana use and its effects on overall approval in potential living kidney donors. Issue 9 (29th July 2022) - Cholin, Liza K.; Delvalle, Christina L.; Fatica, Richard A.; Huml, Anne M.; Augustine, Joshua J.
Abstract: Background: Past and present substance use is an important part of the psychosocial evaluation of potential living kidney donors (LKDs). Increasing state legalizations and social acceptance of marijuana (MJ) use can create challenges for transplant centers. Methods: We investigated the frequency of reporting MJ use, and its effect on the LKD evaluation. A retrospective chart review was performed on all living donor candidates from December 2016 to December 2019 for reports of MJ use, both on an electronic intake form and during clinical evaluation with a licensed social worker (SW). Active MJ use was defined as current use or use within 1 year of evaluation. Baseline characteristics between MJ users and non‐users were compared at each step of donor evaluation. We explored variables associated with MJ use including additional consults and testing during the donor evaluation. Overall approval and donation rates for living donors with active MJ use were compared to non‐users. Additionally, 1‐year donor follow‐up was compared between the two groups. Results of 1818 living donor candidates who completed the intake form, 132 admitted to active MJ use. Compared to non‐users, MJ users were more likely to be younger, male, single, renting a home, and with a lower level of education. Thirty three out of 338 candidates who completed a social work evaluation reported MJ use. Compared to non‐users, MJ users were more frequently classified as moderate or high risk on SW evaluation, and often required a toxicology screen or psychiatry visit for clearance to donate. Altogether 24.2% of MJ users versus 9.5% of non‐users discontinued their evaluation ( p  < .01). Altogether 42.4% of MJ users versus 56.1% of non‐users donated their kidney ( p  = .13). For those who donated, MJ users were less likely than non‐users to follow up at 1 year (57.1% vs. 83.0, p ‐value .02). Conclusion: MJ users were often asked to complete additional steps in their evaluation before an approval decision was made, which may have led to the higher rate of donor drop out observed in this group. Further research is needed to assess the effects of MJ use on living donor candidacy, as well as any effects of MJ use on long‐term donor outcomes.